XRD and SEM characteristics of Co-Ni ferrite nanoparticles Synthesized using sol-gel method - Sabah M. Ali Ridha,Hussam A. Khader (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nickel-doped Cobalt ferrites nanoparticles (NPs) with chemical formula Co1-xNixFe2O4 (were, x= 0, 0.5, and 1) were synthesized at low temperature (200oC) using sol-gel autocombustion technique. Citric acid as a chelating agent used with the mixture of nickel nitrate and ferric nitrate solutions in a ratio of (3:1) to balance the oxidizing agent to reducer ratio. The obtained ferrite NPs were calcined at deferent temperatures (200, 400, 600, and 800°C) for 4h in the air to remove the water content, unwanted impurities and to obtain a single-phase spinel structure with better crystallinity. Structural characteristics of the calcined ferrite NPs were confirm by the analysis of the X-ray diffraction (XRD) technique. XRD analysis shows the single-phase cubic spinel nanocrystalline structure. The crystallite size calculated from FWHM of the strongest peak (311) is in the range of (27-44 nm) for Co1-xNixFe2O4 ferrite NPs. While, the Co0.5Ni0.5Fe2O4 NPs have crystallite size larger than that of NiFe2O4, but smaller than CoFe2O4 NPs. The lattice constant, X-ray density, and other structural parameters calculated from XRD data are in good agreement with the literature values. SEM images show NPs with spherical shape and homogenous morphology with particle size in the range of (25-47 nm), reflecting the highly crystalline nature of these nanoparticles. The average grain size of the samples obtained from SEM images is larger than the crystallite size calculated using XRD measurement, furthermore the distribution of the grains for Cobalt ferrite better than that of Nickel and Co-Ni ferrites. The particle size and grain size of the Co1-xNixFe2O4 ferrite NPs that calculated using XRD and SEM techniques are compatible with each other in the same range